Copper deficiency in a low birthweight infant. Issue 7 (July 1979) - Yuen, P; Lin, H J; Hutchinson, J H
Abstract : Copper deficiency is reported in an infant of very low birthweight. It was characterised by extensive bone changes, severe neutropenia, and hypocupraemia. These manifestations could have been missed but for an intercurrent pneumonia which led to an x-ray of the chest.